Analisis Tanda Visual Kesucian melalui Pendekatan Semiotik: Studi Kasus Kartu Imlek, Natal dan Idul Fitri - Dwi Retno Palupi; Riama Maslan Sihombing (Wimba : Jurnal Komunikasi Visual, 2011)
The religious greeting cards that are based on paper, e-card, e-mail, Short Message Service (SMS), and Multimedia Message Service (MMS) are very beneficial media to strengthen a religious greeting cards is regardes as representation of the value of a related religious celebration itself. Most religious greeting cards use holy visual sign on them, in which it is extremely interesting to be studied. Therefore, this study was concentrated on the use of holy visual sign on Chinese New Year, Christmas, and EID Mubarak greeting cards. This study conducts in semiotics approach. As for the research methodology, this study employed the text analysis that is based on the semiotics approach. This text analysis used to identify and to describe the holy visual signs of the above-mentioned greetings cards. The holy aspect include such things as nature, space and time, commandment and speech, and figure. The study shows that there are some similarities and differences concerning the appearance of holy visual sign on the greeting cards to celebrate Chinese New Year, Christmas, and EID Mubarak. The study also shows that there were some similarities and differences about the meaning of holy visual signs on each of them could be the reasult of the similarities and differences of culturaly, religious background of the people in Indonesia.